Qatar 2022 e sportswashing: un’analisi critica del discorso mediatico italiano - De Feo, Antonietta; Masini, Stefano (Eracle. Journal of Sport and Social Sciences, 2024)
Mega-sport events are often a means used by host countries to enhance their public image or draw attention away from human rights violations. From this point of view, this paper focuses on Qatar 2022, one of the most contested editions in the history of the FIFA World Cup. The authors look to understand how journalistic discourse shapes the processes of legitimisation or contestation of sportswashing practices. The contribution considers the media chronicle of Qatar 2022 in the main newspapers of the Italian sports press, through the methodological tools of Critical Discourse Analysis. The results show residual attention by sports journalism to the controversial aspects of this mega-event, taking into account the system of power relations both within and outside the sports journalism field.